GAMBARAN FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN HIPERTENSI PADA GURU DI SD GMIM IV TOMOHON - Daniel Robert; Phembriah S. Kereh; Meini M. Liuw (Jurnal GIZIDO, 2015)
Hypertension is blood pressure exceeds normal limits is> 140/90 mmHg, hypertension can leadto sudden death or were referred to as the Silent Killer. The World Health Organization said thathypertension is the number 1 cause of death among 7 in the world, in Indonesia hypertensivepatients amounted to 15% of the 230 million population of IndonesiaThe research objective is to describe the factors associated with hypertension in teachers inelementary GMIM IV Tomohon. This research is descriptive, sampling is done by samplingsaturated, the number of 24 people. This study was conducted in May 2015 with a time of 3 dayswhich is housed in SD GMIM IV Tomohon.The results showed an overall total of 24, 41.7% or 10 of them suffer from hypertension. Basedon the results of this study concluded that of the 24 people who responded, the incidence ofhypertension with obesity cases on teachers in elementary GMIM IV Tomohon totaled 8(33.3%), while respondents who did not suffer from hypertension with obesity amount to 8people (33.30%). Respondents suffering from hypertension by having a family history ofdisease, amounting to 5 people (20.83%), while respondents who did not suffer fromhypertension by having a family history of disease, amounting to 8 people (33.3%). Dominanthypertension occurs at age> 40 years by 10 persons (41.7%).